MATHEMATICAL MODELING OF FOURIER TRANSFORM IMAGING SPECTROMETER - N. K. Artioukhina; T. V. Klimovich; M. N. Kotov (Приборы и методы измерений, 2015)
Problems of mathematical modeling of Static Fourier Transform Imaging Spectrometers (SFTIS) for the Earth remote sensing from space are investigated. Rational sequence of the main stages of modeling are proposed. SFTIS mathematical modeling is performed to optimize the features of the instrument.